Impact of deforestation on moisture evaporation from soil and canopy for the territory of Ukraine based on data of numerical experiment LUMIP - Л.А. Писаренко; С.В. Краковська (Геофизический журнал, 2022)
The study presents results of analysis of the impact of partial deforestation on spatio-temporal distribution of the outflow part of water balance, namely evaporation from soil and canopy. The data of 6 Global climate models of theoretical experiment Land Use Model Intercomparison Project (LUMIP) was used in the research. The aim of this experiment is to reveal the influence of global deforestation with further replacement by grass cover on distribution of climate characteristics. It was done for the period 1850—1929, where the first part 1850—1899 refers to the pre-industrial period or period with minimal mostly constant anthropogenic influence; the second part is the next 30 years — 1900—1929. During the pre-industrial period 1850—1899 land cover was reduced globally with a trend of 400 thousand km2 per year and during 1900—1929 it was stable. Defining the impact of deforestation, the normalization over the first 20 years (1850—1869) was performed and there were found anomalies of climatic characteristics as difference to this basic period. Deforestation with further replacement of the forest cover by grass causes an increase in soil evaporation with the trend up to 1.6 mm/10 years in the warm season with more significant changes in April —July, as deforestation reveals more of the soil. Thus, the correlation was −0.8 ...−0.4 between forest cover and soil evaporation with maximal changes in April. It can be connected with grass being sparse in this period but later on covering more soil and preventing intensive evaporation. On the contrary, evaporation from canopy in global climate models is reduced with deforestation as the evaporation area is shrunk. This effect was revealed during all seasons in most grid points, where deforestation occurs. But the biggest change is found in spring and summer months with values up to −0.8 mm/10 years and correlation r = 0.4 ... 0.9 depending on the model and the season. Thus, we found an effect of increasing evaporation from soil while decreasing evaporation from canopy in climate modeling as the effect of partial deforestation on the territory of Ukraine. These changes can cause redistribution in water balance components of the territory and have consequences for hydrological regime, agrometeorology etc. In particular, the increase in soil evaporation due to deforestation can provoke more intensive soil aridization and degradation. The influence of deforestation on total soil moisture and regime of precipitation will be presented in the next publication.